O reuso da informação técnico-científica a partir de um repositório institucional (RJ): um estudo exploratório - Carvalho, Maria da Conceição Rodrigues de (2011)
The present research examined the role of an institutional repository as a new informational environment for housing and disseminating scientific information; produced in the field of research institutions of Science and Technology, by highlighting the purpose of reuse of information and by electing Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) / Fiocruz as a privileged space of research. The transformations in scholarly communication due to the advent of the Internet called for a literature review, which included authors of classical studies on scientific communication, as well as authors who examine these changes in today s society, considering issues such as the movements for open access and digital repository as a political strategy of these movements. Central to these changes, we sought to focus on the concept of reuse of information in its various meanings. Besides Icict, two other repositories were taken as an empirical field research experience, one implemented at Instituto Nacional de Pesquisas Espaciais (INPE) / Brazil and another from the Universidade do Minho / Portugal. For the data collection, questionnaires were applied to teachers who coordinated courses or modules in the post-graduation lato sensu courses of Icict and two interviews were conducted with the managers of the other listed repositories. As a result, it was observed that the institutional repository, although it is a new informational space, has a wide acceptance in the literature and by important actors in the field. It is indicated however, that detailed issues such as copyright and self-archiving should also be addressed. This was confirmed by the scientific literature and by other significant actors of academia and research. As for the reuse of information, it was observed that the theme was recognized as relevant, but poorly focused on by the literature of Information Science and little is known in the academic and informational fields. However, it was noted that the importance of reuse has been recognized as a support for teaching activities. In this way, these teaching activities may benefit from the repository and by the reuse of information. We consider, therefore, that the issue of reuse is a rich field to be explored by studies of the area of Science Information